Anomalous Enhancement of Proton Conductivity for Water Molecular Clusters Stabilized in Interstitial Spaces of Porous Molecular Crystals. Issue 42 (3rd September 2014) - Tadokoro, Makoto; Ohata, Yuki; Shimazaki, Yuriko; Ishimaru, Shin'ichi; Yamada, Teppei; Nagao, Yuki; Sugaya, Tomoaki; Isoda, Kyosuke; Suzuki, Yuta; Kitagawa, Hiroshi; Matsui, Hiroshi
Abstract: In an investigation into the proton conductivity of crystallized water clusters confined within low‐dimensional nanoporous materials, we have found that water‐stable nanoporous crystals are formed by complementary hydrogen bonding between [Co III (H2 bim)3 ] 3+ (H2 bim: 2, 2′‐biimidazole) and TATC 3− (1, 3, 5‐ tricarboxyl‐2, 4, 6‐triazinate); the O atoms in the COO − groups of TATC 3− in the porous outer wall are strongly hydrogen bonded with H2 O, forming two types of WMCs (water molecular clusters): a spirocyclic tetramer chain (SCTC) that forms infinite open 1D channels, and an isolated cyclic tetramer (ICT) present in the void space. The ICT is constructed from four H2 O molecules as a novel C 2 ‐type WMC, which are hydrogen bonded with four‐, three‐, and two‐coordination spheres, respectively. The largest structural fluctuation is observed at elevated temperatures from the two‐coordinated H2 O molecules, which begin to rapidly and isotropically fluctuate on heating. This behavior can be rationalized by a simple model for the elucidation of pre‐melting phenomena, similar to those in ice surfaces as the temperature increases. Moreover, high proton conductivity of SCTCs (ca. 10 −5 S cm −1 at 300 K with an activation energy of 0.30 eV) through a proton‐hole mechanism was observed for pellet samples using the alternating impedance method. The proton conductivity exhibits a slight enhancement of about 0.1×10 −5 S cm −1 at 274 K due to a structural transition upon approaching this temperature that elongates the unit cell along the b ‐axis. The proton‐transfer route can be predicted in WMCs, as O(4) of an H2 O molecule at the center of an SCTC shows a motion that rotates the dipole in the b ‐axis direction, but not the c ‐axis; the thermal ellipsoids of O(4) based on anisotropic temperature factors obtained by X‐ray crystallography reflect a structural fluctuation along the b ‐axis direction induced by [Co III (H2 bim)3 ] 3+ . Abstract : Anomalous proton conductivity : The crystal formed from [Co III (H2 bim)3 ] 3+ and TATC 3− contains two water molecular clusters, a spirocyclic tetramer chain, and an isolated cyclic tetramer (see graphic; H2 bim=2, 2′‐biimidazole, TATC=1, 3, 5‐ tricarboxyl‐2, 4, 6‐triazinate). These clusters have been investigated with regard to their structural chemical water mobilities, proton conductivity mechanism, and structure phase transition.